METHODS OF SELF-ASSESSMENT AND SELF-REFLECTION IN THE FORMATION OF PROFESSIONAL ERUDITION (Ta'limning zamonaviy transformatsiyasi, 2024)
Abstract: This article explores the role of self-assessment and self-reflection methods in the process of forming professional erudition. The author discusses the importance of self-understanding and awareness of one's own knowledge and competencies for the development of professional competence. They analyze various methods of evaluating their own knowledge and experience, as well as methods of self-reflection, including reflective diaries, regular introspection and feedback from colleagues and mentors. As a result of the study, recommendations are presented on the effective use of these methods to increase the level of professional erudition and develop the personal qualities of members of the professional community.